Dissection of the incidence and severity of purple spot physiological disorder in loquat fruit through a physiological and molecular approach - Hadjipieri, Margarita; Georgiadou, Egli C.; Costa, Fabrizio; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2020)
Loquat (Eriobotrya japonica) fruit marketability is affected by the incidence and severity of purple spot (PS), a pre-harvest physiological disorder showing an evident skin discoloration with depressed surface. Despite its impact in limiting the cultivation and economic potential of loquat, the etiology of this disorder is still poorly understood. To this end, our study aimed to investigate and disclose possible mechanisms underlying PS development. The intensity and severity of PS in three loquat cultivars (‘Morphitiki’, ‘Karantoki’ and ‘Obusa’) was phenotypically monitored during successive on-tree fruit developmental stages. ‘Obusa’ fruits harvested at commercial maturity stage showed the highest incidence of purple spot (58.6%), while ‘Morphitiki’ fruits did not show any symptoms. ‘Karantoki’ fruits demonstrated an intermediate response, with 31.3% of the fruit being affected. Thereafter, fruits with 30–50% PS severity were selected and used for further analysis; peel tissue was removed from both symptomatic and asymptomatic tissue of the same fruit for all examined cultivars. ‘Karantoki’ fruit with PS were characterized by the highest accumulation of total soluble sugars, sucrose, glucose and fructose contents, while the concentration of these primary metabolites was the lowest in asymptomatic fruit of ‘Obusa’, exception made for the sucrose. The incidence of PS was also transcriptionally investigated by assessing the mRNA profile of important genes involved in polyphenolic (PAL1, PAL2 and PPO1) and carbohydrate (CWI2, CWI3, SPS1, SPS2, NI2, NI3, SuSy, HXK, FRK and VI) pathway. The enhanced expression levels of CWI3 and VI genes in symptomatic fruit of the highly susceptible cultivar ‘Obusa’ highlight a cultivar-specific type of response. Notably, SuSy registered significantly suppressed levels in symptomatic tissue of both ‘Obusa’ and ‘Karantoki’. To what extent PPO is associated with PS incidence and whether the etiology of the disorder can be assigned to an oxidative process triggered and coordinated by its action need to be further elucidated. The aforementioned genes are suggested to be further examined as potential markers towards a more sophisticated and informed characterization of purple spot detection in loquat fruit.
Keywords: Eriobotrya japonica; Purple spot; Preharvest disorder; Sucrose; Glucose; Fructose; Polyphenol biosynthesis; Candidate gene transcription profiling